“THE IMPACT OF BANKING INFORMATION SYSTEMS APPLICATIONS IN IMPROVING THE QUALITY OF PERFORMANCE–AN EXPLORATORY STUDY FOR A SAMPLE OF IRAQI BANKS” - Asst. Prof. Dr.Fouad Yousif Abdul Rahman (Scholars Digest Publishing, 2023)
The research is based on the idea that banking information systems applications have a significant and effective role in improving the quality of performance of (systems,digital specializations, and decisions) In light of the digital world system and the changing and accelerating banking variables and establish a banking system that able to keep up with the global change movement and the actual need for enhancing the increasing requirements of the clients and provide a better banking service by using of the digital world applications in the banking field , as the research problem, indicated that there is an evident carelessness in transfer from the traditional system to the electronic system of the banking service and improving the quality of the banking performance in keepingup with the change movement and actual need. The research adopted preparing of a questionnaire form and using of five -point Likert scale to get the non-parametric values to solve the problem. The researcher found some conclusions, the most important of which are: There is a significant effect of statistical significance for the applications of banking compliance systems in improving the quality of performance
Keywords: banking information systems applications, improving the quality of performance